Dimerization of an immunoactivating peptide derived from mycobacterial hsp65 using N-hydroxysuccinimide based bifunctional reagents is critical for its antitumor properties - Bezouška, Karel; Kubínková, Zuzana; Stříbný, Jiří; Volfová, Barbora; Pompach, Petr; Kuzma, Marek; Šírová, Milada; Říhová, Blanka (Bioconjugate chemistry, 2012)
We have shown previously that a short pentapeptide derived from the mycobacterial heat shock protein hsp65 can be highly activating for the immune system based on its strong reactivity with the early activation antigen of lymphocytes CD69. Here, we investigated an optimal form of presentation of this antigen to the cells of the immune system. Four different forms of the dimerized heptapeptide LELTEGY, and of the control inactive dimerized heptapeptide LELLEGY that both contained an extra UV active glycine-tyrosine sequence, were prepared using dihydroxysuccinimidyl oxalate (DSO), dihydroxysuccinimidyl tartarate (DST), dihydroxysuccinimidyl glutarate (DSG), and dihydroxysuccinimidyl suberate (DSS), respectively. Heptapeptides dimerized through DST and DSG linkers had optimal activity in CD69 precipitation assay. Moreover, dimerization of active heptapeptide resulted in a remarkable increase in its proliferation activity and production of cytokines in vitro. Furthermore, while DST and DSG dimerized heptapeptides both significantly enhanced the cytotoxicity of natural killer cells in vitro, only the DSG dimerized compound was active in suppressing growth of melanoma tumors in mice and in enhancing the cytotoxic activity of tumor infiltrating lymphocytes ex vivo. Thus, while the dimerization of the immunoactive peptide caused a dramatic increase in its immunoactivating properties, its in vivo anticancer properties were influenced by the chemical nature of linker used for its dimerization.
Keywords: chaperon hsp60; Immunologic Factors; multimerizace proteinu; protinádorové látky; Cell Line, Tumor; Bacterial Proteins; Chaperonin 60; Structure-Activity Relationship; Xenograft Model Antitumor Assays; reagencia zkříženě vázaná; Amino Acid Sequence; vztahy mezi strukturou a aktivitou; peptidové fragmenty; xenogenní modely - testy protinádorové aktivity; Protein Multimerization; Animals; lidé; ženské pohlaví; Humans; zvířata; myši inbrední C57BL; bakteriální proteiny; sekvence aminokyselin; myši; Mice, Inbred C57BL; Cross-Linking Reagents; Succinimides; nádorové buněčné linie; imunologické faktory; sukcinimidy; Female; Mice; Peptide Fragments; Antineoplastic Agents